2008
DOI: 10.1510/icvts.2008.188870
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of antimicrobial activity of slow release silver nanoparticles dressing in post-cardiac surgery mediastinitis

Abstract: We report our preliminary experience in post-cardiac surgery mediastinitis using a recently introduced silver-releasing dressing claiming prompt antibacterial activity. Acticoat, a silver nanoparticles slow release dressing was used in four patients with documented post-cardiac surgery mediastinitis and persistently positive microbiological cultures despite vacuum-assisted closure (VAC) therapy. In all four patients negative cultures were obtained within a maximum of 72 h and patients were discharged within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 4 publications
1
27
0
Order By: Relevance
“…Further treatment of the biofilms without daily transfers (i.e., the batch experiments) resulted in a gradual reduction in viable cell numbers within the biofilms, as independently observed by our group (data not shown) and Percival et al (28), but were in disagreement with previously reported clinical observations (12,33). In contrast, prolonged treatment with daily transfer decreased the efficacies of most tested dressings, resulting in a recovery of the biofilms after 7 days that was consistent with clinical observations (12,41,42). Thus, measuring and predicting the antimicrobial effectivenesses of different silver dressings can be improved by the use of the daily transfer assay to more closely mimic the actual wound bed environment.…”
Section: Discussionsupporting
confidence: 86%
“…Further treatment of the biofilms without daily transfers (i.e., the batch experiments) resulted in a gradual reduction in viable cell numbers within the biofilms, as independently observed by our group (data not shown) and Percival et al (28), but were in disagreement with previously reported clinical observations (12,33). In contrast, prolonged treatment with daily transfer decreased the efficacies of most tested dressings, resulting in a recovery of the biofilms after 7 days that was consistent with clinical observations (12,41,42). Thus, measuring and predicting the antimicrobial effectivenesses of different silver dressings can be improved by the use of the daily transfer assay to more closely mimic the actual wound bed environment.…”
Section: Discussionsupporting
confidence: 86%
“…In all four patients negative cultures were obtained within a maximum of 72 h and patients were discharged within a maximum of 20 days. 63 Hussain et al 64 evaluated the acute toxicity of different metallic nanoparticles in vitro using a rat liver derived cell line (BRL 3A) (ATCC, CRL-1442 immortalized rat liver cells). Different sizes of silver nanoparticles (15 or 100 nm) were evaluated for their potential toxicity.…”
Section: Toxicitymentioning
confidence: 99%
“…The use of a silver-impregnated dressing (with or without concomitant vacuum apparatus) in post-operative mediastinitis with continued positive cultures despite surgical debridement and antibiotic therapy showed conversion to negative cultures and ultimate wound closure with the silver dressing [64]. Another analysis compared mediastinitis rates after cardiac surgery when a silver dressing was used routinely and found a significant decrease in the incidence of infection compared with standard dressings, although the methodology of this study was less rigorous [65].…”
Section: Surgical Incisionsmentioning
confidence: 99%